Removal of Pigment from Textile Wastewater by Electrospun Nanofibre Membrane / Nor Dalila Nor Affand and Nur Najiha Abdul Razak - Nor Affandi, Nor Dalila; Abdul Razak, Nur Najiha (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2020)
The removal of contaminants in textile effluent using electrospun Nylon 6 nanofibre membrane has been investigated in the study. The electrospun Nylon 6 nanofibre membrane was fabricated using electrospinning process at different parameters. The resultant electrospun membrane was characterized for pore diameter and morphological structures. Permeate properties and flux of electrospun Nylon 6 nanofibre membrane were compared with the commercial filter membrane. From the results, it shows that the electrospun Nylon 6 nanofibre membrane exhibited lower flux than the commercial membrane. The accumulation of suspended solid particles onto the electrospun Nylon 6 membrane surface reduced the permeate flux which about 14 minutes slower than the commercial membrane. Although the electrospun Nylon 6 nanofibre membrane exhibited lower flux, this membrane gave the best removal of suspended solids with approximately 99%. As a result, a clear permeate was obtained after the filtration. The electrospun membrane also gave higher reduction of chemical oxygen demand (COD) as compared to the commercial filter membrane. For commercial membrane, it was found that the membrane gave a much lower removal of effluent with approximately 34%. The presence of a large pore diameter of the commercial membrane allows more suspended solids to pass though the membrane, resulting in a cloudy permeate.